2017
DOI: 10.1016/j.ygyno.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

HDAC10 as a potential therapeutic target in ovarian cancer

Abstract: Objective We analyzed histone deacetylase 10 (HDAC10) for function in the context of the DNA damage response in BRCA1-null ovarian cancer cells as well as evaluated the potential of general HDAC inhibitors in primary ovarian carcinoma cells. HDAC10 had previously been shown to be highly stimulatory to the process of homology directed repair in HeLa cells, and in this study we investigated whether HDAC10 could impact in vitro the response to anticancer therapies. We hypothesized that the loss of HDAC10 would se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 39 publications
(57 reference statements)
4
44
0
Order By: Relevance
“…The hydroxamic analogue 10 showed lower selectivity for HDACs 1–3 over HDACs 6 and 8 (Table ), whereas the mercaptosulfide analogue 12 maintained such selectivity but showed the strongest potency against HDAC10 (IC 50 =3.6 n m ), being 10‐ to 25‐fold more active toward this isoform with respect to HDACs 1–3. These results confirmed the importance of the ZBG in the modulation of HDAC inhibitory activity and selectivity profile, and provided some hints about how to address selectivity toward HDAC10, which recently showed to promote lung cancer proliferation and was found to be a potential therapeutic target for ovarian cancer …”
Section: Analogues With Modified Warheadsupporting
confidence: 72%
See 1 more Smart Citation
“…The hydroxamic analogue 10 showed lower selectivity for HDACs 1–3 over HDACs 6 and 8 (Table ), whereas the mercaptosulfide analogue 12 maintained such selectivity but showed the strongest potency against HDAC10 (IC 50 =3.6 n m ), being 10‐ to 25‐fold more active toward this isoform with respect to HDACs 1–3. These results confirmed the importance of the ZBG in the modulation of HDAC inhibitory activity and selectivity profile, and provided some hints about how to address selectivity toward HDAC10, which recently showed to promote lung cancer proliferation and was found to be a potential therapeutic target for ovarian cancer …”
Section: Analogues With Modified Warheadsupporting
confidence: 72%
“…These results confirmedt he importance of the ZBG in the modulation of HDAC inhibitory activity and ChemMedChem 2017ChemMedChem , 12,1917ChemMedChem -1926 www.chemmedchem.org selectivity profile, and provided some hints about how to address selectivityt owardH DAC10, which recently showedt o promote lung cancerp roliferation and was found to be ap otential therapeutic target for ovarian cancer. [24,25] Finally,t he disulfide analogues reported by the same research group highlighted that, by changing the prodrug form of largazole thiol it was possible to modulate the ligands ADME profile, particularlya sr egards the onset of action and oral bioavailability,a ss hown by in vivo histoneh yperacetylation assays in HCT116 cells andm ouse xenograft models. [26] Analogues with modifiedv aline unit…”
Section: Analogues With Modified Warheadmentioning
confidence: 99%
“…In neuroblastoma, the polyamine regulating ODC1 was found co-upregulated with MYCN and correlates with poor outcome in neuroblastoma, suggesting a detrimental role in neuroblastoma biology (Gamble et al 2012; Hogarty et al 2008; Lastowska et al 2007). Moreover, polyamines are known to modulate DNA conformation by strongly binding to the DNA helix (Feuerstein et al 1990; Matthews 1993), and recently identified roles of HDAC10 include regulation of DNA mismatch and DSB repair in various cancer types such as ovarian carcinoma (Islam et al 2017; Radhakrishnan et al 2015). DNA damage has also been described as a result of HDAC6 depletion and inhibition (Namdar et al 2010; Wang et al 2012), and the above-mentioned HDAC8-dependent cohesin complex is well known to accumulate at DNA break sites to mediate DNA repair and recruit cell cycle checkpoint-activating proteins (Caron et al 2012; Watrin and Peters 2009).…”
Section: Discussionmentioning
confidence: 99%
“…HDAC10 was demonstrated to be a tumor suppresser in some types of cancer, including clear cell renal cell carcinoma (13), cervical cancer (19), gastric cancer (12,20), and ovarian cancer (16). The function of HDAC10 in lung cancer is a matter of debate (10,15).…”
Section: Discussionmentioning
confidence: 99%
“…HDAC10 has been reported to be involved in homologous recombination (3), melanogenesis (4), cells autophagy (5-7), cell cycle regulation (8), DNA mismatch repair (9) and cancer progression (10)(11)(12)(13)(14)(15)(16). While HDAC10 was reported to suppresses the proliferation and invasion of clear cell renal cell carcinoma (13), it was also demonstrated to promote cell proliferation via AKT phosphorylation in lung cancer (15).…”
Section: Introductionmentioning
confidence: 99%